Vote buying in Jordanian electoral law: A critical legal analysis of the 2022 legislation - Abu Issa, Hamzeh; Al-Tarawneh, Hasan; Alhrerat, Khalid; Almanasra, Majd (Research Journal in Advanced Humanities, 2025)
The present article aims to analyze vote-buying as a crime under Jordanian Election Law Number 4 of 2022 by studying the relevant legal texts that regulate it, defining its elements, and evaluating their adequacy for preventing this sin. This crime can also fall under the most serious categories of manifest manifestations of political corruption because it directly corrupts the popular will and jeopardizes the legitimacy of the electoral process. The article’s concern is whether the current text of law confronts the phenomenon of vote-buying with the required efficacy, given the evolution of the ways of committing it and the bounds of judicial interpretation. The research is descriptive and analytical while making a comparison with the earlier legal texts and analyzing the relevant decisions of the Jordanian Court of Cassation. The current law does possess important advancements, particularly not requiring the status of a candidate for the commission of the crime and introducing a penalty of disqualification from candidacy. However, there are still deficiencies in some respects, such as the failure to criminalize attempts and a lack of awareness of electronic images of the crime. The research recommends amending the text to include attempts, increasing penalties in organized cases, expanding liability to include electoral lists, and updating evidence tools to enhance the effectiveness of the enforcement of the legal text and ensure the integrity of elections.